Behavioral mechanism of transfer and dispersal of Propylaea japonica in cotton adjacent to sorghum fields - Cui, Hongying; Li, Lili; Song, Yingying; Guo, Wenxiu; Lv, Suhong; Yu, Yi; Men, Xingyuan (Frontiers in Sustainable Food Systems, 2023)
Increasing crop biodiversity, such as by adjacent managed crops, is recognized as an effective biological control measure. However, few studies have focused on the mechanisms involved in how adjacent managed crops increase natural enemy populations, leading to reduced pest numbers. This study investigated the hypothesis that cotton grown adjacent to sorghum would positively influence the feeding and oviposition preferences of the ladybug Propylaea japonica, which predates cotton aphids, leading to enhanced pest control. The populations of Aphis gossypii were significantly lower and those of P. japonica were significantly higher in cotton grown adjacent to sorghum compared with monoculture cotton fields. Regardless of diet on which the larva of P. japonica were reared (Melanaphis sacchari, A. gossypii, and 50% M. sacchari + 50% A. gossypii), the adults always consumed significantly more M. sacchari compared with A. gossypii. P. japonica also showed significantly higher feeding and oviposition preferences for host plants bearing aphids to only host plants. P. japonica fed M. sacchari preferred to lay eggs on cotton, whereas those fed A. gossypii preferred to lay eggs on sorghum. These results suggest that the habitat of natural enemies can be expanded by influencing their feeding and oviposition preferences to achieve pest control in adjacent cropping systems. This research, which incorporates field and laboratory studies, suggests an approach for the successful conservation and biological control of cotton aphids using adjacent managed cotton and sorghum crops.